Structural and Functional MRI Differences in Master Sommeliers: A Pilot Study on Expertise in the Brain - Banks, Sarah J.; Sreenivasan, Karthik R.; Weintraub, David M.; Baldock, Deanna; Noback, Michael; Pierce, Meghan E.; Frasnelli, Johannes; James, Jay; Beall, Erik; Zhuang, Xiaowei; Cordes, Dietmar; Leger, Gabriel C. (Frontiers in Human Neuroscience, 2016)
Our experiences, even as adults, shape our brains. Regional differences have been found in experts, with the regions associated with their particular skill-set. Functional differences have also been noted in brain activation patterns in some experts. This study uses multimodal techniques to assess structural and functional patterns that differ between experts and nonexperts. Sommeliers are experts in wine and thus in olfaction. We assessed differences in Master Sommeliers’ brains, compared with controls, in structure and also in functional response to olfactory and visual judgment tasks. MRI data were analyzed using voxel-based morphometry as well as automated parcellation to assess structural properties, and group differences between tasks were calculated. Results indicate enhanced volume in the right insula and entorhinal cortex, with the cortical thickness of the entorhinal correlating with experience. There were regional activation differences in a large area involving the right olfactory and memory regions, with heightened activation specifically for sommeliers during an olfactory task. Our results indicate that sommeliers’ brains show specialization in the expected regions of the olfactory and memory networks, and also in regions important in integration of internal sensory stimuli and external cues. Overall, these differences suggest that specialized expertise and training might result in enhancements in the brain well into adulthood. This is particularly important given the regions involved, which are the first to be impacted by many neurodegenerative diseases.